'Nobody cares about the environment': Kyrgyz' perspectives on enhancing environmental sustainable consumption practices when facing limited sustainability awareness. (23rd September 2014) - Shadymanova, Jarkyn; Wahlen, Stefan; van der Horst, Hilje
Abstract Within Western societies, the detrimental consequences of mass consumption on the environment have long been identified. Consumers have developed sustainability consciousness in accordance with research and policies. In non‐Western societies, however, experiences with mass consumption have not been so long standing. Furthermore, the extent of mass consumerism is not as wide ranging as in many of the richer countries in the world. In central Asian countries, a soviet history adds to this the concept of resource depletion and sustainability impacting industrialization as an ideological taboo. Currently, central Asian countries such as Kyrgyzstan are embarking on enacting sustainability policies. Kyrgyz consumers are also developing sustainability awareness. This awareness sometimes leads to either new practices or changes in existing practices. However, consumption practices are too complex to assume that only consciousness will lead to increasingly sustainable practices. Furthermore, there is no control over the content of such awareness. The case of emergent sustainable consumption in Kyrgyzstan demonstrates how sustainability values become integrated with locally existing knowledge, meanings and material circumstances. The intent of this study is to investigate how Kyrgyz consumers perceive sustainable consumption and whether and how they integrate sustainability awareness into practices and with other values. Our data consist of 50 structured interviews that were conducted during the summer of 2013 in the Kyrgyz capital of Bishkek. Closed questions were analysed employing descriptive statistics, whereas a qualitative content analysis was applied to the results of open questions. The results provide an insight into the way in which emerging sustainability awareness is able to develop and how such awareness becomes integrated into existing practices and values.